Directional Ostwald Ripening for Producing Aligned Arrays of Nanowires - Lee, Hye Jin; Yang, U. Leong; Kim, Kyeong Nam; Park, Soojin; Kil, Kye Hyoung; Kim, Jun Soo; Wodtke, Alec M.; Choi, Won Jun; Kim, Myung Hwa; Baik, Jeong Min (AMER CHEMICAL SOC, 2019)
The remarkable electronic and mechanical properties of nanowires have great potential for fascinating applications; however, the difficulties of assembling ordered arrays of aligned nanowires over large areas prevent their integration into many practical devices. In this paper, we show that aligned VO2 nanowires form spontaneously after heating a thin V2O5 film on a grooved SiO2 surface. Nanowires grow after complete dewetting of the film, after which there is the formation of supercooled nanodroplets and subsequent Ostwald ripening and coalescence. We investigate the growth mechanism using molecular dynamics simulations of spherical Lennard-Jones particles, and the simulations help explain how the grooved surface produces aligned nanowires. Using this simple synthesis approach, we produce self-aligned, millimeter-long nanowire arrays with uniform metal-insulator transition properties; after their transfer to a polymer substrate, the nanowires act as a highly sensitive array of strain sensors with a very fast response time of several tens of milliseconds.
Keywords: CHEMICAL-VAPOR-DEPOSITION; ZNO NANOWIRES; PHASE-TRANSITION; QUANTUM WIRES; VO2 NANOBEAM; GAS SENSORS; STRAIN; PRESSURE; GROWTH; TRANSPARENT